A LAW ATTEMPT TO RESOLVE THE VACUUM OF NORM BY FORMULATION PERPPU AS A NEW LEGAL FORMATION RELATED TO THE IMPLEMENTATION OF INTERIM REPLACEMENTS IN SPECIAL SITUATIONS - Ni Nyoman Putri Purnama Santhi; Hendij Ana Widowati (JOURNAL OF LAW AND NATION, 2024)
The existence of mass or collective corruption cases committed by DPRD legislators in the current legal reality has caused a vacuum in the legislature and stagnation in the administration of local government. DPRD legislators who have been identified as defendants must resign through the mechanism of inter temporal replacement (PAW). Principally, the problem is that the rights of these defendants are still protected by law because there has been an unincracht decision. This is the case of the legal studies issues raised in this paper. The research used in this writing is normative legal research because there are problems with the condition of vacuum norms so that new laws and regulations are needed to regulate the stagnation of local government administration due to mass corruption. Furthermore, it is necessary to establish a new law, namely Government Regulation in Lieu of Law (Perppu) as a new legal norm that regulates special situations. In terms of overcoming if similar legal problems will occur again at a later time, then the provisions in the Perppu will apply and otherwise the MPR, DPR, DPRD, and DPD Law (MD3 Law) is not applicable in the special situation problem, as the use of the principle of lex posteriori derogat legi priori applies.